Impact of Information Technology on Tax Administration in Southwest, Nigeria (Global Journal of Management and Business Research, 2017)
This study examined the impact of information technology on tax administration in south west, Nigeria. It specifically investigated the effect of information technology on tax productivity and the relationship between information technology ontax implementation and tax planning. Descriptive research design was employed, of which questionnaire was used to gather data and analysed with multiple regression and pearson product moment correlation. The study revealed that information technology (Online Tax Filing-OTF, Online Tax Registration-OTR and Online Tax Remittance-OTRE) affect tax productivitywith -1.9%, 7.3% and 31.5% (p=0.85, 0.526 and 0.00), there isrelationship of -5.9% (p=0.520),9.7% (p=0.290) and 0.344 (p=0.000) between OTF,OTR and OTRE on Tax Implementation-TAXIMP and -3.8% (p=0.684), 14% (p=0.140) and -0.190 (p=0.038
Keywords: tax administration; tax productivity; information technology; online tax filling; online tax remittance; online tax registration